The “Relevance Gap” in Islamic Education: Arabic E-Learning and the Islamic Sciences - Baihaqi, M.; Nuha, Ahmad Nur Ulin; Rosi, Fathor; Rifki, Ahmad; Fathani, Ahmad; Alfatawi, Ahmad Talkhis; Ramadhani, Arya Pratama (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2025)
The twenty-first century has transformed the way Islamic knowledge is accessed, mediated, and acquired, and Arabic-as the foundational language of the Islamic sciences-sits at the centre of this transformation. While Android-based e-learning applications now offer abundant, attractive, and accessible Arabic learning materials, it remains unclear whether these materials are genuinely relevant to the epistemological demands of the Islamic sciences (al-ʻulūm al-sharʻiyyah) or whether they merely treat Arabic as a generic foreign language. Drawing on Krippendorff’s qualitative content analysis, this study examines six purposively selected applications-Learn Arabic, Bahasa Arab Sehari-hari, Learn Arabic for Islamic Studies, Belajar Bahasa Arab Anak, Quranic Arabic, and AlifBee-against a five-dimension analytical rubric covering content relevance, instructional design, integration with the Islamic sciences, user engagement and accessibility, and epistemological alignment. The findings reveal a persistent “relevance gap”: the applications are technologically mature and pedagogically engaging but epistemologically shallow, prioritising conversational fluency and usability over the morphological, syntactic, and interpretive competencies required to engage classical texts. The study argues that closing this gap requires the collaborative design of curriculum-integrated materials that embed Arabic within a coherent Islamic epistemological framework rather than appending Islamic vocabulary to a secular language-learning template.